Correlation Relationship Between Physical Abilities And The Accuracy Of Forehand Shot In Squash - Mutasher, Firas; Issam, Farah (Journal of Physical Education, 2018)
Correlation Relationship Between Physical Abilities And The Accuracy Of Forehand Shot In Squash The researcher aimed at identifying the type of relationship between physical abilities (strength and flexibility) with the accuracy of forehand shot in squash. The researchers used the descriptive method. The subjects were (6) squash players from the national league. The data was collected and treated using proper statistical operations to conclude that there is a correlation relationship between the training program physical abilities (strength and flexibility). In addition to that there are weaknesses in the physical abilities of players in strength and flexibility. The researchers recommended deigning a training program for developing the accuracy of motor performance.